EMPOWERING HEALTHY FOOD PRODUCTION OF "SOY BOB" SOY MILK FOR SMALL BUSINESS GROUPS IN MANGUNHARJO TEMBALANG SEMARANG - Fatimah Fatimah; Siti Masrochah (Wealth Community Empowerment, 2024)
This Soy Bob product is different from the soy milk that is usually circulated and known to the public. On the other hand, all works do not have patents or copyrights with their unique characteristics, as well as packaging management and marketing efforts. Likewise, this small soy milk culinary business is managed traditionally, both packaging and not having an AKG value, expired, as well as marketing efforts. Therefore, the aim of this community service is expected to be to strengthen the quality of small business products in the Mangunharjo Tembalang area. The population for this activity was residents of RW V, Mangunharjo Tembalang Village. The method used in this activity was a training approach, followed by program implementation by assisting certification, licensing and there was an evaluation at each stage will be carried out to obtain feedback and further improvement efforts. The results and discussions of this activity were the awareness and understanding of visitors regarding health and the importance of consuming soy milk and the NIB registration for Soy Bob soy milk had been registered. In addition, the NIB and PIRT registration guide for Small Businesses had been compiled, Soy Bob product booklets and books had been copyrighted. The conclusion from this activity was that it could be carried out well. There was increasing public awareness of the importance of "Soy Bob" soy milk for health. For this reason, it is necessary to increase the motivation of the assisted villages to produce other healthy food and drink products to improve health as well as to increase the income of the assisted villages.